Efeito do carregamento de hidrogênio no comportamento eletroquímico de diferentes aços de alta resistência e baixa liga (ARBL) e da super liga Inconel 718 (UNS N07718) - Resende, Mariani de Ávila (2021)
One of the main causes of failure in steels is due to the permeation of hydrogen that is absorbed, resulting in changes in the mechanical properties and in the reduction of the plastic deformation capacity, leading to brittle fractures. Electrochemical techniques can be used to measure hydrogen permeation and interaction in metallic materials. Therefore, the Devanathan-Stachurski electrochemical cell was used to determine the solubility, permeability and diffusivity values of hydrogen in AISI steels and in superalloy UNS N07718. This nickel coating was carried out by electrodeposition in a 0.91 M NiSO4 solution; 0.13M NiCl2; 0.32M H3BO4; 0.11 M CH3COOH and 0.5 mM sodium lauryl sulfate, applying a current density of -10 mA cm-2 for 10 min. The electrodeposited nickel presented a homogeneous and shiny appearance. From the atomic force microscope, the formation of a granular, regular and low roughness nickel film was observed. The steel that showed the highest concentration of hydrogen retained in borate buffer at -7mA cm-2 was AISI 4137-M in 3.5% NaCl medium and AISI 4130-M and AISI 4137-M in TB and 0.01M EDTA and the lowest was AISI 4130-M in 3.5% NaCl at -10 mA cm-2. In the curves of hydrogen permeation with successive permeations, an increase in the value of the anodic current of hydrogen oxidation of the second permeation was observed in relation to the first for the AISI ,4137-M and 4130-M, steels due to the filling of the irreversible entrapment sites in the first permeation. From the electrochemical characterization of the steels after hydrogen permeation, it was found that the value of the stabilized open circuit potential shifts to more negative values and there is a decrease in the values of resistance to charge transfer, suggesting that the hydrogen altered both the surfaces of steels and nickel superalloy.